2013
DOI: 10.1096/fj.13-236356
|View full text |Cite
|
Sign up to set email alerts
|

The role of the cytoskeleton in sensing changes in gravity by nonspecialized cells

Abstract: A large body of evidence indicates that single cells in vitro respond to changes in gravity, and that this response might play an important role for physiological changes at the organism level during spaceflight. Gravity can lead to changes in cell proliferation, differentiation, signaling, and gene expression. At first glance, gravitational forces seem too small to affect bodies with the size of a cell. Thus, the initial response to gravity is both puzzling and important for understanding physiological change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
126
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(136 citation statements)
references
References 106 publications
8
126
0
2
Order By: Relevance
“…Comparing the weight of a single cell with the other physical forces within a cell, it is unlikely that the cell can detect the vector of gravity. Searching for the initial gravity sensor, research has been focusing mainly on the cytoskeleton [47]. A popular model for how cells can sense mechanical forces (and possibly gravitational changes) is the idea that the cell cytoskeleton is built in tensegrity architecture, which provides the cell's stability.…”
Section: Resultsmentioning
confidence: 99%
“…Comparing the weight of a single cell with the other physical forces within a cell, it is unlikely that the cell can detect the vector of gravity. Searching for the initial gravity sensor, research has been focusing mainly on the cytoskeleton [47]. A popular model for how cells can sense mechanical forces (and possibly gravitational changes) is the idea that the cell cytoskeleton is built in tensegrity architecture, which provides the cell's stability.…”
Section: Resultsmentioning
confidence: 99%
“…The balance between tensional forces and the cytoskeleton architecture modulates thereupon several complex cell functions like apoptosis, differentiation, proliferation, ECM remodelling, and so forth [31]. Compelling data demonstrated that both simulated and real, space-based microgravity can severely affect cytoskeleton structure and function [8, 32]. The most impressive modifications were observed in nonadherent RPM-exposed cells in which stress fibers disappear and actin architecture is severely compromised, thus jeopardizing the chances of cell anchoring to the substrate.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, relevant modifications in tissue organization have been recorded in microgravity-exposed organs and/or animals [5, 6]. Shape changes are likely to be mediated by concomitant structural rearrangement of cytoskeleton (CSK), which is severely disorganized under microgravity [7, 8]. CSK conveys mechanical signals into the cells, and by that way it influences both biochemical pathways [9, 10] and gene expression [11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…These results provide an insight how altered gravity regulates the functions of neutrophils and the underlying mechanisms which mediate the innate immune responses for long-term, manned spaceflight. Grenon et al 2013; bFGF ↓ HDTBR, head-down-tilt bed rest; RWV, rotating wall vessel (i.e., RCCS used in the current work); RPM, random positioning machine IL, interleukin; G-CSF, granulocyte-macrophage colony-stimulating factor; MIP-1α, macrophage inflammatory protein-1α; MCP-1, monocyte chemotactic protein 1; TNF-α, tumour necrosis factor-α; IFN-γ , Interferon-γ ; TGF-β, transforming growth factor-β; bFGF, basic fibroblast growth factor LFA-1, lymphocyte function-associated antigen-1; Mac-1, macrophage-1 antigen; ICAM-1, VLA-4, very late antigen 4; PSGL-1, P-selectin glycoprotein ligand 1; ICAM-1, intercellular cell adhesion molecule-1; PECAM-1, platelet/endothelial cell adhesion molecule 1; VCAM-1, vascular cell adhesion molecule 1 NO, nitric oxide; eNOS, endothelial nitric oxide synthase H 2 O 2 , hydrogen peroxide; ROS, reactive oxygen species Legend: ↑, increased; ↓, decreased; -, unchanged The cytoskeletal proteins have been proposed as potential gravity sensor, and significant changes of cytoskeletal network have been observed under microgravity environment both during spaceflight and in ground-based simulation techniques (Vorselen et al 2014). Although we have not seen obvious disorganization of the F-actin under the effects of simulated microgravity, the cell shape changes of HL-60 cells (Fig.…”
Section: Discussionmentioning
confidence: 99%